Association Between Household Food Security And Nutritional Status Among Children Age Under 5 Years In Flood Prone Area, Sukolilo, Surabaya - durry, fara disa; Handini, Laksmi Suci; Seliana, Irma; Febriawan, Zulfan; Sari, Lilik Nurindah; Santoso, Shaira Nadinda; Yudinda, Salsabilla Cathabell; Nahya, Fibran Aryan Nahya; Novendra, Gala; Syahbaa , Zebaa Basyaasyah Baarigh; Arianti, Novi Rahayu (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2024)
Household food insecurity (HFI) is a significant issue that affects both developed and developing countries, leading to various health and nutritional problems. Particularly concerning is the impact of food insecurity on young children, who are highly vulnerable to malnutrition and stunting. Sukolilo is a flood-prone area, and flooding can cause changes in household food security and impact the nutritional status of children. This study to determine the association between household food security and the nutritional status of toddlers in Sukolilo. This study used a cross-sectional method by collecting data on household characteristics (parents' age, education, number of children, parents' employment status, and total income), measuring household food security through the Household Food Insecurity Access Scale (HFIAS) questionnaire, and measuring anthropometry (W/A) in toddlers to analyze nutritional status. The results showed that there is a significant relationship between mother education level (P = 0.03), number of children (P = 0.000), and mother employment status (P = 0.000) with household food security (p < 0.05). As well as there is an association between household food security and children's nutritional status (P<0.05) (AOR (95% CI) 0.86 (0.77 – 1.73)). It can be concluded that household food security has a strong relationship with the nutritional status of toddlers.